PENATAAN KEWENANGAN MENTERI BADAN USAHA MILIK NEGARA DALAM PENETAPAN KOMISARIS BADAN USAHA MILIK NEGARA - suhela arnis; Dessy Artina; Meriza Elpha Darnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
As a rule of law based on the values of Pancasila and the 1945 Constitution ofthe Republic of Indonesia, State-Owned Enterprises (BUMN) as part of separated stateassets are in order to carry out the function of state prosperity and welfare by using theconcept of a welfare state approach. which is mandated by the Constitution Article 33Paragraph (2) and Paragraph (3) of the 1945 Constitution. With the very vital role ofcommissioners in the company, the non-optimization of the board of commissioners inthe BUMN structure will indirectly reduce the quality of BUMN in achieving BUMNgoals.With the phenomenon of multiple positions, the appointment of ex-convicts incorruption cases as commissioners of BUMN, and the determination of BUMNcommissioners from non-professional circles suspected of being politically appointed,show and the need for structuring the authority of the BUMN minister in determiningthe appointment of BUMN commissioners.This research was conducted with the type of normative juridical research,namely research carried out by examining secondary legal materials or research basedon standardized rules that have been recorded which is also called, with doctrinalresearch or library research.Research results, The first is the authority of the Minister of BUMN inassigning commissioners to BUMN which is attributive (original). The second isthe need for the role of the state in carrying out government functions in structuring theauthority of the Minister of BUMN in determining BUMN commissioners andstrengthening the principles of good corporate governance. Suggestions from theauthorFirst, it is expected that the Minister of BUMN will appoint a BUMNcommissioner based on the criteria has been determined. Second, according to theauthor,According to the author, the requirements and procedures for appointingand dismissing members of the BUMN board of commissioners must be regulatedin the form of a law so that these rules are more binding,and the government actiontaken by the BUMN minister to appoint a BUMN commissioner must be seen asagoverment action so that it remains the object of supervision of the House ofRepresentatives (DPR).Keywords :Authority, Minister, Commissioner and State-owned enterprises